Report of the Working Group on Implementation of Population Policy and Achieving Rapid Population Stabilization for the Tenth Five Year Plan - Planning Commission (Planning Commission, 2001)
Population pressure is an underlying cause of over-exploitation of natural resources like land, water, forests etc. Spiral linkages amongst excessive population growth, extremes of poverty and prosperity, and environmental degradation have drawn increasing attention of Indian planners, population scientists, ecologists, and environmentalists over the recent past. Stabilizing population has been enshrined as an essential requirement for promoting sustainable development with equitable distribution in the National Population Policy,2000 (NPP-2000) document released by the Department of Family Welfare, Ministry of Health and Family Welfare(MOHFW), Govt. of India at the beginning of New Millennium. The NPP document affirms the commitment of government towards stabilizing population by 2045, as it’s long term objective, which would facilitate economically, environmentally and socially sustainable development.
Government of India Planning Commission
Government of India Planning Commission